College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.6 - Transformations of Functions - 2.6 Exercises: 63

Answer

$g(x)=(x-2)^{2}=x^{2}-4x+4$

Work Step by Step

We obtain $g(x)$ by shifting $f(x)=x^2$ two units to the right, i.e. $y=f(x-2)$: $g(x)=(x-2)^{2}=x^{2}-4x+4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.